Estimation of distributed flow resistance in vegetated rivers using airborne topo‐bathymetric LiDAR and its application to risk management tasks for Asahi River flooding - Yoshida, Keisuke; Maeno, Shiro; Ogawa, Shuhei; Mano, Koji; Nigo, Shinya (Journal of flood risk management, 2020)
This report describes a method of extracting vegetation conditions and topo‐bathymetric data of rivers using airborne LiDAR with near‐infrared and green pulsed lasers. Parameters related to flow resistance attributable to vegetation in rivers were found using point cloud data of LiDAR with support from supervised classification. Comparison of data obtained from simulations and observations was used to assess the applicability of the proposed method for examination of lower Asahi River flooding that occurred in Japan in September 2011. Results demonstrated that the methodology used herein can estimate flow resistance parameterisation of vegetation distributed on a reach scale. This study also used numerical tests to elucidate effects of established vegetation for flood control at the lower Asahi River bifurcation point using a historically important fixed weir. Results of these numerical tests demonstrated that the method can elucidate effective means of managing vegetation removal around the bifurcation point.